Pengaruh Infrastruktur PU terhadap Perekonomian dan Kesejahteraan di Sumatera dan Jawa - Sukma, Andrio Firstiana; Hartono, Djoni (Jurnal Sosial Ekonomi Pekerjaan Umum, 2009)
Infrastructure is one of the efforts to improve services to support the embodiment of the people welfare. Therefore, infrastructure services should be improved in line with the demands of development and better public services. This is also supported by a number of studies that show that infrastructure can endorse economic growth. In particular PU, infrastructure plays a very important role in economic growth. Referring to that, then this paper will attempt to analyze the influence of PU infrastructure to the economy and welfare in Java and Sumatra. Method used in this research is the inpur-output analysis, econometric analysis and social analysis. The results are that the PU infrastructure was indeed had a positive impact on economic growth and encourage the establishment of welfare and also playing a part in encouraging creation of social capital. If views per sector, Bina Marga sector are the sector that the most absorbing labor while water resources sector is the sector that was most encouraged economic growth.